Porous Nanofiber Membrane: Rational Platform for Highly Sensitive Thermochromic Sensor (Adv. Funct. Mater. 24/2022). (8th June 2022) - Kim, Dong‐Ha; Bae, Jaehyeong; Lee, Jiyoung; Ahn, Jaewan; Hwang, Won‐Tae; Ko, Jaehyun; Kim, Il‐Doo
Abstract : Porous Nanofiber Membranes In article number 2200463, Il‐Doo Kim and co‐workers develop highly sensitive thermochromic sensors using nanofiber (NF) membranes with tunable alignments of the NFs via a fine‐tuned electric field during the electrospinning process. The porous NFs membrane‐based sensors show highly sensitive thermochromic sensing performance at 31.6–42.7 °C. The developed NFs sensors membranes could be further integrated with masks, patches, and bracelets for wearable applications.